Hợp đồng hành chính - Thái, Phạm Hồng (VNU Journal of Science: Social Sciences and Humanities; Vol 15 No 2, 1999)
The article pays attention to analyse the concept and the characters of adm inistration contract. The author showed th at the adm inistration contracts has been considered as a contract form applying in our country and this concept is perfected day by day.